+0  
 
0
247
2
avatar

-6 + f = 2 f=8, what are the steps for this?

Guest Jun 4, 2017
 #1
avatar+7002 
+1

I assume that you meant -6 + f = 2f - 8

\(-6+f = 2f-8\\ f-6=2f-8\\ f+2=2f\\ 2 =f\\ f=2\)

MaxWong  Jun 4, 2017
 #2
avatar+7155 
0

If you meant:

Does     -6 + f = 2     if     f = 8         ?

 

-6 + f   \(\stackrel{?}{=}\)   2

 

Replace  " f "  with  " 8 "  .

-6 + 8   \(\stackrel{?}{=}\)   2

 

Simplify left side of equation.

2   \(\stackrel{?}{=}\)   2

 

2   =   2        true

 

Yes,     -6 + f = 2     if     f = 8  .

hectictar  Jun 4, 2017

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.